2015
DOI: 10.1073/pnas.1421290112
|View full text |Cite
|
Sign up to set email alerts
|

Ionic imbalance, in addition to molecular crowding, abates cytoskeletal dynamics and vesicle motility during hypertonic stress

Abstract: Cell volume homeostasis is vital for the maintenance of optimal protein density and cellular function. Numerous mammalian cell types are routinely exposed to acute hypertonic challenge and shrink. Molecular crowding modifies biochemical reaction rates and decreases macromolecule diffusion. Cell volume is restored rapidly by ion influx but at the expense of elevated intracellular sodium and chloride levels that persist long after challenge. Although recent studies have highlighted the role of molecular crowding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 81 publications
0
40
1
Order By: Relevance
“…Thus, TUDC exerts its choleretic effect by a coordinated insertion of both Ntcp and Bsep into plasma and canalicular membrane, respectively. A recent study showed that vesicle motility and ATP production is transiently reduced in a variety of cell types, including hepatocytes after treatment with hyperosmotic medium (65). Movement of dextran-loaded endosomes was tracked by live-cell imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, TUDC exerts its choleretic effect by a coordinated insertion of both Ntcp and Bsep into plasma and canalicular membrane, respectively. A recent study showed that vesicle motility and ATP production is transiently reduced in a variety of cell types, including hepatocytes after treatment with hyperosmotic medium (65). Movement of dextran-loaded endosomes was tracked by live-cell imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Because dextran is distributed to early, late, and recycling endosomes, this approach, however, will not distinguish between differences in motility among these compartments. Whether the motility is restricted also in newly endocytosed vesicles therefore remains unclear (65).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we are intrigued that we now find protein-to-protein association of NFAT5, with many proteins involved in effects of hypertonicity, but not known to be transcriptional targets of NFAT5. Thus, hypertonicity interrupts the cell cycle (9), and NFAT5 associates with numerous proteins involved in cell proliferation (see RESULTS); development is aberrant in NFAT5 Ϫ/Ϫ fetuses (37,40), and NFAT5 associates with proteins involved in development (see RE-SULTS); hypertonicity affects activity of numerous enzymes (19), and we find that NFAT5 associates with several enzymes (see RESULTS); hypertonicity affects the cytoskeleton (8,39,45,48), and NFAT5 associates with cytoskeletal proteins and their regulators (see results); hypertonicity affects mitochondria (42,54,56), and NFAT5 associates with mitochondrial ribosomal proteins, transporters and structural proteins. We do not know whether and, if so, how protein-to-protein association of NFAT5 with these other proteins affects them, but the association raises interesting questions.…”
Section: Discussionmentioning
confidence: 72%
“…In order to test whether or not [Cl − ] i can modulate IL‐1β expression, we used a double ionophore strategy (ionophores nigericin and tributyltin) that equilibrates the intracellular and extracellular chloride and H + concentrations [Krapf et al, ], while keeping constant the pH, cell volume [Nunes et al, ], and membrane potential (since these ionophores are non‐electrogenic) [Antonenko Yu, ; Orlov et al, ]. In these conditions, the extracellular and intracellular Cl − concentrations are equal [Krapf et al, ; Valdivieso et al, , ].…”
Section: Resultsmentioning
confidence: 99%